The Examination System Quality and Information Quality in the Use of the JKN Mobile App - Mitha Mandasary; Mieke Nurmalasari; Hosizah Hosizah; Tria Saras Pertiwi (Jurnal Infokes, 2026)
Background: The Mobile JKN application enables BPJS Kesehatan participants to access health services, including online outpatient registration. At Jampangkulon Hospital, 13,021 of 28,896 outpatient visits (44.92%) were registered through Mobile JKN between January and June 2025. Despite increasing use several system related issues persist underscoring the need to evaluate the system and information quality supporting the application. Objective: This study aimed to assess the association of system quality and information quality on the utilization of the Mobile JKN. Methods: The study adopted a cross-sectional analytical design and involved 388 Mobile JKN users selected through accidental sampling. The data were collected using a validated and reliable questionnaire with a four-point Likert scale and analysed through multiple linear regression. The Mobile JKN use was evaluated using five indicators: frequency, duration, intensity, nature, and pattern. Results: The result showed that system quality (b= 0.204; 95% CI: 0.11–0.29; p < 0.001) and information quality (b= 0.547; 95% CI: 0.47–0.63; p < 0.001) were positively and significantly associated with application use. Conclusion: The model explained 71.2% of the variance in application use (R² = 0.712). Suggestion: Hospital Manajemen and BPJS Kesehatan should continue improving the system to encourage wider adoption.